Analysis of social support among adolescents with excess body weight - Rinaldi, Tainara; Arielle Eissmann, Jennifer; Arlindo de Sousa, Clovis; Regina Lima Duarte da Silva, Cláudia; Maria Vargas, Deisi; Coutinho de Azevedo, Luciane (O Mundo da Saúde, 2020)
Social support refers to the material and psychological resources that people have access to through social networks. This is an important and poorly studied aspect in adolescents with chronic health conditions. This study aimed to analyze the global social support and its domains in overweight adolescents. Nutritional status, food intake and global social support, along with its domains, were assessed using anthropometric measurements, a food frequency questionnaire for adolescents and the Medical Outcomes Study instrument, respectively. Seventy-one adolescents participated in the study, 52.7% women and 47.2% men. Most were overweight (71.83%) and with a high abdominal circumference (76.47%). Approximately half of the interviewees were classified as having low global social support (50.7%), with no differences between the categories of body mass index and waist circumference. The group classified as having a high global social support had greater calorie, carbohydrate, and lipid intake than those with less support. There was a positive statistical correlation between the values attributed to carbohydrate intake and the values scored in the global social support (r = 0.33; p = 0.26), the interaction domain (r = 0.33; p = 0.23) and the information domain (r = 0.40; p = 0.006). A positive association was observed between the values of caloric intake and those of the information domain (r = 0.34; p = 0.20). The overweight adolescents evaluated showed a high frequency of low social support and positive correlations were identified between calorie intake and global social support score, as well as between carbohydrate intake and scores in the interaction and information domains.